2013
DOI: 10.3402/ijch.v72i0.20723
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of vitamin D in a northern Canadian Dené First Nation community

Abstract: BackgroundIncreased awareness of the wide spectrum of activity of vitamin D has focused interest on its role in the health of Canada's Aboriginal peoples, who bear a high burden of both infectious and chronic disease. Cutaneous vitamin D synthesis is limited at northern latitudes, and the transition from nutrient-dense traditional to nutrient-poor market foods has left many Canadian Aboriginal populations food insecure and nutritionally vulnerable.ObjectiveThe study was undertaken to determine the level of die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The non-synthesizing season mean 25(OH)D was above the highest NHANES III subgroup ( 42 ). However, this report is consistent with findings for indigenous adults residing in northern circumpolar regions where seasonality and local foods are important mediators of vitamin D intake ( 43 ) and circulating 25(OH)D concentration ( 27 , 44 48 ). Pronounced seasonality of serum 25(OH)D has been demonstrated among 47 adult Caucasians residing in Fairbanks, Alaska, latitude 65°N, based on 12 months of longitudinal sampling and was shown to follow measured UV-B exposure, although intake appeared to be a more important factor than sunlight for determining year-round concentrations ( 49 ).…”
Section: Discussionsupporting
confidence: 90%
“…The non-synthesizing season mean 25(OH)D was above the highest NHANES III subgroup ( 42 ). However, this report is consistent with findings for indigenous adults residing in northern circumpolar regions where seasonality and local foods are important mediators of vitamin D intake ( 43 ) and circulating 25(OH)D concentration ( 27 , 44 48 ). Pronounced seasonality of serum 25(OH)D has been demonstrated among 47 adult Caucasians residing in Fairbanks, Alaska, latitude 65°N, based on 12 months of longitudinal sampling and was shown to follow measured UV-B exposure, although intake appeared to be a more important factor than sunlight for determining year-round concentrations ( 49 ).…”
Section: Discussionsupporting
confidence: 90%
“…Fish, egg yolk, cheese, and mushrooms are the only dietary sources that contain natural vitamin D (12). Among these, fish has, in general, the highest content of vitamin D (12,13) and is the major natural food source in many populations within (14)(15)(16)(17) and outside of (18,19) Europe. Other significant food sources are fortified items such as margarine, skimmed milk, and orange juice (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for exclusion included the absence of reported obesity rate ( n =36), the use of CCHS or other national data ( n =30) (here are a few noteworthy examples: [28, 48–53]), the sample not being representative of a whole population ( n =67) as in the case of studies whose participants are restricted to a specific age group [42, 43, 5456], focus on pregnant women [5762], diabetes screening initiatives [41, 63–66], and the inclusion of nondiabetic persons only [67, 68]. Studies presenting findings that have already been reported in the 17 unique studies retained for this article ( n =64) were also excluded, as well as those using a definition of obesity other than BMI ≥ 30 ( n =7) [6975] and those for which reviewers were unable to find the full-text article ( n =3) [76–78]. Of the seven studies using a definition of obesity other than BMI ≥ 30, two presented obesity as BMI ≥ 27 [72, 74], another two combined overweight and obesity (BMI ≥ 25) [73, 75], a further two studies solely presented mean BMI [70, 71], and one last study only used abdominal obesity, which was measured using waist circumference.…”
Section: Resultsmentioning
confidence: 99%
“…Studies presenting findings that have already been reported in the 17 unique studies retained for this article ( n =64) were also excluded, as well as those using a definition of obesity other than BMI ≥ 30 ( n =7) [6975] and those for which reviewers were unable to find the full-text article ( n =3) [76–78]. Of the seven studies using a definition of obesity other than BMI ≥ 30, two presented obesity as BMI ≥ 27 [72, 74], another two combined overweight and obesity (BMI ≥ 25) [73, 75], a further two studies solely presented mean BMI [70, 71], and one last study only used abdominal obesity, which was measured using waist circumference. A further 22 papers were identified in the grey literature search, 19 of which met inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%